A case of primary cutaneous Ewing sarcoma in a neutropenic patient. (16th January 2019) - Brown‐Joel, Zoe O.; Bellizzi, Andrew M.; Darbro, Benjamin W.; Snow, Anthony N.; Tanas, Munir R.; Keeney, Matthew E.; Stone, Mary S.; Wanat, Karolyn A.; Roth, Gretchen M.
Abstract : Primary cutaneous Ewing sarcoma is a rare clinical presentation of Ewing sarcoma, usually occurring as a small, localized tumor on the extremities of young adults and associated with favorable prognosis. We report a case of primary cutaneous Ewing sarcoma, which presented on the sole of the foot of a 27‐year‐old patient with relapsed acute myeloid leukemia and neutropenia. Diagnosis was determined through histological features and staining, as well as fluorescence in situ hybridization and molecular testing. The patient underwent wide‐local excision with plan to begin targeted chemotherapy, but unfortunately died from adenovirus pneumonia while neutropenic before targeted chemotherapy was initiated.